Training Evaluation: Clients Roles - Hashim, Junaidah (Emerald Group Publishing Limited, 2001)
Training evaluation is an elusive concept, especially when it comes to practice. The practice of evaluation in training has received a lot of criticism. This criticism is largely explained by the unsystematic, informal, and ad hoc evaluation that has been conducted by training institutions. In Malaysia, training activities are monitored by the government. Organisations are required to obtain training services from approved training providers registered with the government. Examines the clients’ demand toward evaluation, the commitment given by training providers, and the overall practice of evaluation by the training providers in Malaysia. Finds that the government, client and economic situations have influenced the evaluation practice in a positive direction.